One versus two adjacent interdigital neuroma excision: a patient outcome study - Benjamin, Kefilwe Boineelo; Saragas, Nikiforos; Ferrão, Paulo (Journal of the Foot & Ankle, 2021)
Objective: We aimed to evaluate patient satisfaction after surgery for both single and two adjacent neuromas. Methods: We reviewed the data of patients treated operatively for interdigital neuromas between 2003 and 2016. We interviewed them and administered the Self-Reported Foot and Ankle Score questionnaire. Patient scores were then analyzed categorically, and variation between groups was assessed. Results: Sixty-two patients were available for review. Thirty-one patients had a single interdigital neuroma excised and 31 had two adjacente interdigital neuromas excised. Twenty-eight of the 31 (90%) patients with a single neuroma had good or excellent results while 23 (74.2%) of those with adjacent neuromas had similar outcomes. One patient with a single neuroma had a poor result while four patients with adjacent neuromas had poor results. The mean score was 41 (excellent) for patients with a single interdigital neuroma and 37 (good) for those with adjacent neuromas (p=0.473). The majority of patients in both groups would undergo surgery again. Conclusion: We found no statistically significant difference in outcomes of patients who undergo surgery for either single or two adjacent interdigital neuromas. General patient satisfaction is good and/or excellent post excision. Level of Evidence II; Prognostic Studies; Retrospective Study.